Rare bird documentation form for Greater Scaup at Coralville Reservoir, 1977 - Halmi, Nicholas S.et al (1977)
Rare bird documentation form for a Greater Scaup at Coralville Reservoir in Johnson County, IA on March 22, 1977. Epson - sheet feed